RHYTHM AS THE MAIN COMPONENT OF MUSIC-RHYTHMIC EDUCATION OF THE JUNIOR SCHOOLCHILD - Дудик, Р.В. (SWorldJournal, 2022)
Theses consider the issue of musical and rhythmic education of the children. It is emphasized that mastering and using rhythmic exercises in music lessons significantly stimulates creative activity of students. It is emphasized that the correct use of mea